(untitled) (Salud, Arte y Cuidado, 2024)
Objective: to implement group techniques to promote the appropriate behavior of family members towards their patients with Fibromyalgia. Method: The current research responds to a type of interventional and descriptive study. Implemented to relatives of patients with fibromyalgia who were assisted at the Roberto Infante Pascual Hospital in the period January-2021 to January-2022; under the methods: constructive-interpretive, observation and medical interview; instruments: group techniques. Through the mixed methodology and verticalized by the phenomenological paradigm. Results: The distribution of relatives of patients with Fibromyalgia according to age and sex predominated between 46-56 years (75%) and the predominant sex was female (62.5%). Relatives of patients with Fibromyalgia according to level of knowledge of Fibromyalgia, inadequate knowledge predominated before the intervention with 87.5% and after the sessions with group techniques there was greater adequate knowledge with 83.3%. The distribution of relatives of patients with Fibromyalgia according to Knowledge about the indicated treatment, inadequate knowledge predominated before the intervention with 83.3% and after the sessions there was a greater incidence of adequate knowledge with 79.1%. Conclusions: With the level of knowledge adequately acquired by the family member who participated in the interventions, it contributed to a better quality of life in patients with fibromyalgia by facilitating palliative skills towards the resigned; All of the above allowed a favorable rhythm for the patient in their quality of life, work and social activity